Vokhum Fest: A Specialized Integrated Marketing Communication Event towards Small Medium Enterprises Brand Management and Youth Social Welfare - Hardika Widi Satria; Maudisha Alifa Rahman; Friska Arifiani; Fitriyah Nurzakiyah (Jurnal Sosial Humaniora Terapan, 2020)
Integrated Marketing Communication is an essential concept in marketing field. It is used worldwide to marketing and communicating in vary kind of business both in big enterprise or small enterprise. This article describes the implementation of IMC on an event marketing called Vokhum Fest as a community engagement program. The event is a collaborationbetween Vocational Education Program Universitas Indonesia lecturers, assistant lecturers, students and 12 Small Medium Enterprises (SMEs) in Jakarta Greater Area ranging from products to services also for the most part organized by youth. It argues that IMC plan contribute positively to SMEs brand management and its social welfare by generating income in short term and manage long term brand value. The method of this study is qualitative by means of interview and observation within 12 SMEs in Jakarta Greater Area. The paper argues that SMEs brand resonances better throughout online amplification of digital marketing, yet it also requires offline activity to engage with the consumer, customer,prospect, employee and stakeholders in public by establish event marketing such as Vokhum Fest.Keywords: Integrated Marketing Communication, Small Medium Enterprise, Brand Management, Digital Marketing, Event Marketing, Youth, Social Welfare.